2018
DOI: 10.3390/su10061912
|View full text |Cite
|
Sign up to set email alerts
|

Greenhouse Gas Emission Intensities for the Livestock Sector in Indonesia, Based on the National Specific Data

Abstract: Abstract:The aims of this study were to calculate greenhouse gas (GHG) emissions and to identify the trends of GHG emission intensity, based on meat production from the livestock sector in Indonesia, which had not been done before. The total emissions from the livestock sector from 2000 to 2015 in Indonesia were calculated using the 2006 Intergovernmental Panel on Climate Change Guideline (2006 IPCC GL) using Tier 1 and Tier 2, with its default values and some of the country specific data that were found in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 8 publications
1
11
0
2
Order By: Relevance
“…Reduction of greenhouse gas emission is considered as an arduous and urgent task for the Chinese livestock industry [18]. Despite of different methods of IPCC Tier 1 (constant EFs) and Tier 2 (dynamic EFs) [19,20], the present study obtained similar temporal patterns of annual CH4 emissions (10-36 Gg) (Figure 3a). However, the annual CH4 emissions in this study derived from the lower dynamic EFs were approximately 13-19% lower than the previous results [12] based on the constant EF before 2010 (Figure 3).…”
Section: Temporal Ch4 Emission Of Livestock and Poultry Farmingsupporting
confidence: 61%
“…Reduction of greenhouse gas emission is considered as an arduous and urgent task for the Chinese livestock industry [18]. Despite of different methods of IPCC Tier 1 (constant EFs) and Tier 2 (dynamic EFs) [19,20], the present study obtained similar temporal patterns of annual CH4 emissions (10-36 Gg) (Figure 3a). However, the annual CH4 emissions in this study derived from the lower dynamic EFs were approximately 13-19% lower than the previous results [12] based on the constant EF before 2010 (Figure 3).…”
Section: Temporal Ch4 Emission Of Livestock and Poultry Farmingsupporting
confidence: 61%
“…Usually, countries where CH 4 emissions are predominant have a relatively high proportion of animal production; thus, they have high CH 4 emissions due to enteric fermentation. The exception is Indonesia, where the main cereal produced is rice, whose cultivation accounts for most of the CH 4 emissions; a relatively small amount of CH 4 emissions comes from animal production [ 61 ].…”
Section: Resultsmentioning
confidence: 99%
“…In the emission inventory for South, South East and East Asia for 2000 [11], cattle was the largest emitter for CH 4 , N 2 O and NH 3 emissions, with a share of 56%, 30% and 33% respectively. Study of Reference [32] in Indonesia has also shown cattle as the major contributor to GHG emissions in the 2005-2015 period. Our results provide a reminder that regarding agricultural sector emission mitigation, policies in the Red River Delta should not be copied from other countries.…”
Section: Discussionmentioning
confidence: 99%